Investigating Local Brand Satisfaction: A Case Study of Bandung, West Java - Meliana, Vina; A. Sumbogo, Ignatius; Ruminda, Marthaleina; Parlindungan, Purbanuara; Sibuea, Sondang (KnE Social Sciences, 2023)
The city of Bandung has enormous potential to grow its local brands. This study aimed to investigate local brand satisfaction based on two key factors, the city of origin being Bandung and electronic service quality. This study used descriptive quantitative methods and questionnaires from 210 respondents who had purchased a bodypack model bag product from any enterprise in Bandung. The data analysis technique used was multiple regression. The results showed that the city of origin and electronic service quality affects, both partially and simultaneously, customer satisfaction. Keywords: country of origin, electronic service quality, customer satisfaction, creative industry